Experimental plans method to formulate a self-compacting cement paste - Mebrouki, Abdelkader (Materiali in tehnologije, 2010)
This paper presents a self-compacting cement-paste formulation using Algerian local materials (a binary cement consisting of natural pozzolana and limestone fillers). In this study, simple laboratory instruments were used, i.e., a mini-slump for spreading out diameters and a Marsh cone for flow-times measurements. A wide variation of combinations was used as preliminary tests to select pastes with acceptable properties and the use of the mixture-plans method has shown that it is possible to define an experimental field inside which optimal measurements can be obtained. This field has been put mathematically into equation form, conditioned by implicit constraints, defining zones of minimal shearing threshold and maximum viscosity and was then solved numerically. The optimization criterion was checked in addition to the interactivity between the components utilizing the multiple combinations of proportioning these materials. From the results given by the ternary diagrams and desirability functions, an optimal self-compacting cement-paste mixture was defined. Experimental checking was performed to validate the obtained results.
Keywords: malte; cementni materiali; beton; polnila; zgoščevanje